Analisis pemanfaatan tanaman obat terhadap penyembuhan penyakit - Azzahra, Zahwa Fatimah (Maliki Interdisciplinary Journal, 2025)
The utilization of medicinal plants as an alternative treatment has been practiced for a long time, rooted in the community’s knowledge of the plants’ efficacy. Indonesia, with its high biodiversity, has many plant species that have the potential to become medicine. Leaves from various plants, such as guava, cat whiskers, betel leaf, papaya, sambiloto, green cincau, and soursop, contain bioactive compounds that have been proven effective in alleviating various diseases and enhancing health. The processing of plants into safe medicines involves selecting appropriate methods and applying strict safety standards. While medicinal plants offer a natural alternative, modern medicine, based on scientific research, provides faster results for serious conditions. The collaboration between the two can enhance treatment effectiveness, although challenges in dosage standards and training for healthcare practitioners need to be addressed.